2018
DOI: 10.3846/jcem.2018.300
|View full text |Cite
|
Sign up to set email alerts
|

Validating DFS concept in lifecycle subway projects in China based on incident case analysis and network analysis

Abstract: Abstract.Regardless of potential benefits of design for safety (DFS) concept for lifecycle safety management in construction industry, DFS adoption as an early intervention has been slower than expected. While existing research mainly concentrates on construction and operation phases, the role of design phase in construction safety management is always ignored. To validate the influence of DFS concept on lifecycle safety performance, this research conducted an incident case analysis (ICA) based on 442 cases co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 52 publications
1
14
0
Order By: Relevance
“…Through the analysis of all of the indicator scores, shown in Table 3 , it was discovered that the dimension of engineering survey and design (D1) achieved the top score. Consistent with the current studies concerning subway construction safety [ 59 , 60 ], the engineering survey and design dimension (D1) is believed to be the key factor influencing subway construction accidents in China. In addition, four out of the 10 top indicators were located in the engineering survey and design dimension ( Figure 2 ).…”
Section: Discussionsupporting
confidence: 59%
“…Through the analysis of all of the indicator scores, shown in Table 3 , it was discovered that the dimension of engineering survey and design (D1) achieved the top score. Consistent with the current studies concerning subway construction safety [ 59 , 60 ], the engineering survey and design dimension (D1) is believed to be the key factor influencing subway construction accidents in China. In addition, four out of the 10 top indicators were located in the engineering survey and design dimension ( Figure 2 ).…”
Section: Discussionsupporting
confidence: 59%
“…the complexity of project could lead to extensive design changes) (Larsen and Whyte, 2013). This is supported by Xiahou et al (2018), where they emphasised that the nature of project, for example in subway project, the design activities have a greater influence on the operation, rather than the construction phase. In contrast, proactive actions on PtD practices are required in both stages (design and underground operations management) for hazard preventions (firedamp, asbestos, radioactive minerals, etc.…”
Section: Experiencementioning
confidence: 99%
“…Construction safety literatures across the world have indicated the strong link between design and the occurrence of injuries and accidents in construction (Behm, 2005;Manu et al, 2014;Toh et al, 2017;Hardison and Hallowell, 2019). For instance, a recent study of subway projects in China by Xiahou et al (2018) found that 53% of the accidents could be linked to safe design. Studies by Driscoll et al (2008) and Hui (2015) found that 44% of construction fatalities were "design-related" in Australia and Singapore, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The main basis of the metro construction process is the design scheme. It can be said that the safety hazard is also designed [77]. Therefore, engineering design defects or errors will directly cause safety risks.…”
Section: Determination Of Influencing Factors Of Safety Risk In Metromentioning
confidence: 99%